2003
DOI: 10.1055/s-2003-41127
|View full text |Cite
|
Sign up to set email alerts
|

In vivoAnti-Inflammatory and Antinociceptive Effects of Liriodendrin Isolated from the Stem Bark ofAcanthopanax senticosus

Abstract: In the present study, liriodendrin isolated by activity-guided fractionation from the ethyl acetate (EtOAc) extracts of the stem bark of Acanthopanax senticosus, was evaluated for anti-inflammatory and antinociceptive activities. Liriodendrin (5, 10 mg/kg/day, p. o.) significantly inhibited the increase of vascular permeability induced by acetic acid in mice and reduced an acute paw edema induced by carrageenan in rats. When the analgesic activity was measured by the acetic acid-induced writhing test and hot p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(25 citation statements)
references
References 12 publications
(15 reference statements)
0
25
0
Order By: Relevance
“…The lignan compound syringaresinol has been shown to inhibit inflammation in lipopolysaccharide-treated macriohages (Jung et al, 2003), gastric ulcer (Fujikawa et al, 1996), and oxidative injury of endothelial cells (Liu et al, 2009). Our previous results showed that another lignan compound sesamine promoted eNOS phosphorylation and NO production, which plays an important role in endothelial cell survival and angiogenesis (Chung et al, 2010), indicating that lignan compounds can increase NO production via eNOS phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…The lignan compound syringaresinol has been shown to inhibit inflammation in lipopolysaccharide-treated macriohages (Jung et al, 2003), gastric ulcer (Fujikawa et al, 1996), and oxidative injury of endothelial cells (Liu et al, 2009). Our previous results showed that another lignan compound sesamine promoted eNOS phosphorylation and NO production, which plays an important role in endothelial cell survival and angiogenesis (Chung et al, 2010), indicating that lignan compounds can increase NO production via eNOS phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicated that the isolated compounds from ES inhibit the NOS2 as well as COX2 expression 65,66. However, it has also been shown that 80% ethanol extract from ES attenuated LPS-induced NOS2 expression but not COX2 expression 20.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have already reported on the anti-inflammatory effects of components from A. sessiliflorus [11,12]. Since NO is known to play an important role in the inflammatory process, inhibitors of NO production are considered as potential anti-inflammatory agents [22].…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have provided evidence for the anti-inflammatory effects of extracts and components from Acanthopanax species [10,11,12]. Therefore, isolated compounds 1 − 9 were evaluated for anti-inflammatory activities through the measurement of nitrite, a soluble oxidation product of nitric oxide (NO), in lipopolysaccharide (LPS)-induced RAW 254.7 macrophage cells.…”
Section: Introductionmentioning
confidence: 99%